Comparison of Incidental Thyroid Nodules Between Early Breast Cancer Patients and Healthy Controls: Higher Incidence and Thyroid Imaging Reporting and Data System (TI-RADS) Score of Patients with Cancer. - Raoufi, Masoomeh; Anbiaee, Robab; Soltani, Zohre; Shojaeian, Fatemeh; Safavi-Naini, Seyed Amir Ahmad (International Journal of Cancer Management, 2021)
Background: Breast and thyroid cancers remain among the most common malignancies in women. In previous studies, the cooccurrence of thyroid and breast cancers has been reported. Objectives: The aim of this study was to evaluate and compare the risk and incidence of incidental thyroid nodules (ITNs) between patients with breast cancer and healthy controls, based on the Thyroid Imaging Reporting and Data System (TI-RADS). Methods: This case-control study was conducted on 140 patients with breast cancer and 140 cancer-free women in a similar age range. Thyroid ultrasonography (US) was performed before the onset of treatment. The risk stratification of thyroid nodules was based on the TI-RADS. Results: The mean age of the participants was not significantly different between the case (43.35 - 7.85 years) and control (42.11 - 3.69 years) groups (P = 0.094). Invasive ductal carcinoma was the most frequent type of breast cancer in the patients. Normal thyroid US findings were significantly less frequent in patients with breast cancer (35.7%) compared to the healthy controls (76.4%) (P = 0.001). On the other hand, thyroid nodules were more frequent in the patients and associated with a higher risk of malignancy (i.e., high TI-RADS scores) compared to healthy women (P = 0.001 and P = 0.001, respectively). Besides, patients with breast cancer showed more thyroid abnormalities in the US examinations. Conclusions: A higher frequency of ITN, with an elevated TI-RADS score, which raised the suspicion of malignancy, was seen in patients with breast cancer. Overall, patients with breast cancer may benefit from a regular thyroid US examination.